Faith and resistance in the age of Trump - De La Torre, Miguel A. (Maryknoll, New York : Orbis Books, 2017)
For many people of faith, the election of Donald Trump represents not just a political crisis -- a threat to our republic and a danger for the entire world -- but also a confessional crisis, a moment that calls into question the deepest meaning of our religious claims and values. Reflections by notable religious scholars, ministers, and activists address this crisis. With chapters treating issues of gender, race, disability, LGBT justice, immigration, the environment, peace, and poverty, the contributors seek to name our situation and to set forth an agenda for faith and resistance.
Foreword: Sustainability and solidarity in the Trump era / Jim Wallis -- Preface: A call to resistance / Jacqui J. Lewis -- Introduction: r
Includes bibliographical references and index.
Keywords: Trump, Donald, -- 1946- -- Public opinion; Christianity and politics -- United States -- History -- 21st century; Public opinion; History